The international economics of natural resources and growth - Thorvaldur Gylfason (Center for Economic Studies and ifo Institute (CESifo), 2007)
This article is in three parts. First, it briefly describes the contribution of natural resources to economic growth around the world, pondering the question whether an abundance of natural resources is a blessing or a curse. Second, an attempt is made to provide a glimpse of recent empirical evidence that can be brought to bear on this question. Third, the article discusses the experience of Norway, the world's third largest oil exporter. To date, Norway has appeared to be mostly free of the worrisome symptoms, such as the Dutch disease, that have afflicted many other countries with abundant natural resources.
Keywords: O11; 330; Rohstoffressourcen; Natürliche Ressourcen; Wirtschaftswachstum; Dutch Disease; Schätzung; Welt; Erdölpolitik; Good Governance; Norwegen